An approach to the process of urbanization in Baja California Sur during the porfirian period: the case of San Jose del Cabo (Tzintzun, Revista de Estudios Históricos, 2016)
The purpose of this paper is to explain the process of urbanization inBaja California Sur during the porfirian period, specificaly in San Jose delCabo, A town, which is located at the southern part of the peninsula. Weresumed the idea that urban is a space that is characterized by the existenceof a regular merchant trade, political and administrative function andrelatively differentiated social organization. The next is divided into foursections where you can see that the urbanization process involved a legalorder as the basis of the organization of space and the provision of publicservices.
Keywords: San Jose del Cabo; urbanization; space